Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.12968/hmed.2020.0604
|View full text |Cite
|
Sign up to set email alerts
|

Use of a proforma to improve documentation of the post-take ward round and encourage initiation of the comprehensive geriatric assessment in the care of the older people's service

Abstract: Aims/Background The post-take ward round is often the first time that a senior clinician reviews a patient on the acute medical take. Despite this, there is no official guidance regarding structure or documentation of the post-take ward round. The aim of this quality improve project was to develop a ward round proforma specifically tailored to the care of the older people's service to improve quality of documentation and to encourage initiation of the comprehensive geriatric assessment. Methods An initial audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, the use of a structured round (that is, one that includes checklists and clinical decision-making aids, such as is included in a rounding proforma) can enhance the quality of care and consistency in documentation. [3][4][5] Through a Plan-Do-Study-Act (PDSA) approach, this project has two aims. First, to measure the adherence of documentation to the Royal College of Physicians (RCP) best practice guidelines and predetermined key unique components of a stroke round (see Table 1).…”
Section: Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of a structured round (that is, one that includes checklists and clinical decision-making aids, such as is included in a rounding proforma) can enhance the quality of care and consistency in documentation. [3][4][5] Through a Plan-Do-Study-Act (PDSA) approach, this project has two aims. First, to measure the adherence of documentation to the Royal College of Physicians (RCP) best practice guidelines and predetermined key unique components of a stroke round (see Table 1).…”
Section: Problemmentioning
confidence: 99%
“…However, the use of a structured round (that is, one that includes checklists and clinical decision-making aids, such as is included in a rounding proforma) can enhance the quality of care and consistency in documentation. 3–5…”
Section: Introductionmentioning
confidence: 99%
“…This model fosters a more patient-centered and e cient care approach, reducing the need for investigations and overall hospital usage (BGS, 2019, Leahy et al, 2021, Veronese et al, 2022. Ideally, a multidisciplinary assessment proforma should underpin the intervention plan enhancing the quality and consistency of documentation and promoting Comprehensive geriatric Assessment (CGA) initiation (Xu et al, 2021). Barry et al (2023) identi ed speci c barriers and facilitators to screening adults in emergency care settings (ED's, AAUs), forming the foundational synthesis for this study-the rst focused on screening in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…Visibility of screening impact and addressing con icting screening goals are essential components. The value of proformas in informing and underpinning older person-centred care are well recognised within the literature(Xu et al, 2021; BGS, 2019, HSE, 2017. Participants within this study unanimously favoured a comprehensive CGA proforma.…”
mentioning
confidence: 99%
“…Similarly, multiple studies have demonstrated improvement in documentation, when measured against set criteria, following the introduction of a proforma for medical post-take ward rounds [ 5 - 7 ]. Other reported benefits of ward-round checklists in medical settings include a reduction in the time spent in documentation by junior medical staff [ 8 ] and an increase in the initiation of comprehensive geriatric assessment following admission [ 9 ].…”
Section: Introductionmentioning
confidence: 99%